Childhood, Literature, and Science
1 online resource (320 pages)
Keywords: "How do we understand, imagine and remember childhood? In what ways do cultural representations and scientific discourses meet in their ways of portraying children? Childhood, Literature and Science aims to answer these questions by tracing how images of childhood(s) and children in Western modernity are entangled with notions of innocence and fragility, but also with sin and evilness. Indeed, this interdisciplinary collection investigates how different child figures emerge or disappear in imaginative and social representations, in the memories of adult selves, and in expert knowledge. Questions about childhood in western modernity, culture and science are also addressed through insightful analysis of a variety of materials from the Enlightenment age to the present day--such as fiction, life narratives, visual images, scientific texts and public writings.Analysing childhood as a discursive construction, Childhood, Literature and Science will appeal to scholars as well as undergraduate and postgraduate students interested in fields such as: Childhood Studies, History, Gender Studies, Cultural Studies, Literature and Sociology of the Family."--Provided by publisher.